Perancangan Kursi Untuk Memperbaiki Posisi Kerja Guna Meningkatkan Produktivitas Studi Kasus di PG Jatibarang Brebes - Rachmawati, Putri; Sokhibi, Akh (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2019)
PG. Jatibarang Brebes is the first company directly under the BUMN (Badan Usaha Milik Negara)Â  company. this is company produces sugar of Central Java region which is under PTPN IX. There are six stages in the process of producing sugar, namely the milling stage, purification stage, evaporation stage, crystallization stage, the stage of rotation and finishing. The last activity is the packaging of sugar into the sack of 50 kg carried by the operator who sits on a sack with irregular heights. Seen from the aspect of ergonomic seating position is not very suitable because sugar packaging operators work in an uncomfortable position. Therefore, it is necessary to design seats for ergonomic sugar packaging operators. The method used to design this chair is with the concept of ergonomics. The required data include anthropometric data of operator body size, operator complaint during work, packaging process time during work. Then the data is processed to be applied to the design. The design is a prototype which will be measured and compared the output results in the conditions before and after the design was applied. The standard of production output was increased from 384,6 sacks/hour to 454.5 sacks/hour (18,17%) after the new design chair has been applied.